THE IMPORTANCE OF DIGITAL TECHNOLOGIES IN THE DEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP (American Journal of Business Management, Economics and Banking, 2025)
This article is devoted to a comprehensive analysis of the possibilities, problems, and prospects for the development of the small business and private entrepreneurship sector of Uzbekistan in the context of the digital economy. The study examines the mechanisms of the impact of digital transformation on small businesses, an analysis of the current situation, foreign experience, and best practices. The digital economy creates enormous opportunities for small businesses: expanding market boundaries, reducing operating costs, and introducing new business models. Although digital transformation is developing rapidly in Uzbekistan, the level of use of digital technologies in the small business sector lags behind the indicators of developed countries. The article presents proposals for developing digital literacy programs, creating financial support mechanisms, and improving infrastructure to accelerate the digitalization of small businesses.